2023
DOI: 10.1186/s12903-023-02938-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of web-based Arabic health information on dental implants: an infodemiological study

Abstract: Background In the era of the internet, patients seek health information ahead of getting the required treatment. Dental implant, which is among the most sought dental treatments, is not an exception. Incorrect health related information may lead to harmful deeds, so this study sought to assess the quality of web-based Arabic health information on dental implants. Methods The following engines were searched: Google (http://www.google.com), Yahoo! (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
6
13
2
Order By: Relevance
“…For the DISCERN categories, moderate scores were the most common, and high scores were mostly in universities or medical centers. These findings are consistent with other studies, but the percentage of high-quality websites was higher for websites in this study [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…For the DISCERN categories, moderate scores were the most common, and high scores were mostly in universities or medical centers. These findings are consistent with other studies, but the percentage of high-quality websites was higher for websites in this study [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…The Arabic WBHI on OLP in this study included a higher percentage of resources deemed to be of higher quality compared to Arabic WBHI on other diseases, including periodontal diseases and breast and oral cancers [ 12 , 14 , 34 ]. For instance, in this study, 1 in every 5 WBHI sources had fulfilled all 4 JAMA benchmarks, while recent results by Halboub et al [ 16 ] and Al-Ak’hali et al [ 34 ] found the same for 8% and 4%, respectively, of the websites they reviewed. The association of higher quality with resources classified as academic was noted in previous studies evaluating Arabic WBHI [ 34 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Some global research indicates that the quality of some WBHI targeting the public could be of low quality [ 10 , 11 ]. Evidence that examined Arabic WBHI often found that a considerable proportion of the WBHI had low quality, including but not limited to not disclosing the authorship of the information, outdated information, and lack of advice that WBHI should not replace a health care consultation [ 12 - 16 ]. Often, high-quality WBHI would require payment (ie, subscription) for access, exacerbating the inequalities in accessing WBHI for some individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach ensures comparability and appropriates application of readability assessment in Arabic texts. [ 28 30 ].…”
Section: Methodsmentioning
confidence: 99%